Evaluation of Antimicrobial Activity, Cytotoxicity, and Phytochemical Composition of Ocimum americanum L. (Lamiaceae). (17th March 2022) - Ali, Hashim; Nguta, Joseph; Musila, Fredrick; Ole-Mapenay, Isaac; Matara, Dorine; Mailu, James
Abstract : Background . Herbal plants are a natural source of novel biomolecules used widely in ethnomedicine. The present study was intended to examine the antimicrobial properties, cytotoxicity, and phytoconstituents of Ocimum americanum L., an herb traditionally used by the people of Swahili (Kenya) against microbial infections. Methods . The aerial parts of Ocimum americanum L. were sourced, dried, milled, and extracted using three solvents: aqueous, acetonic, and 70% hydroethanolic. Additionally, fractions of chloroform and ethyl acetate were obtained from all crude extracts of the plant. The antimicrobial property was evaluated using agar well diffusion and microdilution techniques against human opportunistic pathogens including S. aureus, E. coli, and C. albicans . The brine shrimp cytotoxicity test was used to analyze the lethality of the extracts and fractions. Phytochemical screening was used to qualitatively assay the presence of phytoconstituents. Results . The phytochemical assay confirmed the presence of alkaloids, phenols, flavonoids, tannins, saponins, terpenoids, reducing sugars, anthraquinones, and glycosides. The lethality test demonstrated that all the extracts and fractions were toxic against Artemia salina nauplii with LC50 values ranging from 0.59 to 559.71  µ g/ml. Chloroformic fraction of the hydroethanolic extract had the highest lethality with an LC50 value of 0.59  µ g/ml. Two of the extracts and their fractions displayed antimicrobial activity against the Gram-positive bacteria ( B. cereus and S. aureus ) and fungus ( C. albicans ), while the same extracts had no activity against the Gram-negative bacteria ( E. coli and K. pneumoniae ). The highest antimicrobial activity was seen in the ethyl acetate fraction of the hydroethanolic extract at 250 mg/ml against Bacillus cereus which had an inhibition zone of 26.00 ± 0.00 and MIC value of 62.5 mg/ml. Conclusion . In the current study, we report that Ocimum americanum L. demonstrated moderate antimicrobial activity, contains numerous phytocompounds, and is highly cytotoxic; thus, further research is needed for bioprospecting a novel compound.